2010
DOI: 10.1111/j.1365-3164.2009.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for atopic dermatitis in dogs: a systematic review of randomized controlled trials

Abstract: The objective of this systematic review, which was performed following the guidelines of the Cochrane collaboration, was to assess the effects of interventions for treatment of atopic dermatitis (AD) in dogs. Citations identified from three databases (MEDLINE, Thomson’s Science Citation Index Expanded and CAB Abstracts) and trials published by December 2007 were selected. Proceedings books from the major veterinary dermatology international congresses were hand searched for relevant citations. The authors sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
159
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(173 citation statements)
references
References 48 publications
(174 reference statements)
5
159
0
9
Order By: Relevance
“…In human medicine, cyclosporine is an immunosuppressant drug used for organ transplant patients to decrease the risk of organ rejection [6]. In veterinary medicine, cyclosporine has been widely used for dermatologic diseases and other systemic immune-mediated diseases [1,2,13,16]. Recent reviews and a meta-analysis of prospective clinical trials concluded that cyclosporine was highly effective compared with placebo and was as effective as prednisolone for treatment of atopic dermatitis in the dog [13,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In human medicine, cyclosporine is an immunosuppressant drug used for organ transplant patients to decrease the risk of organ rejection [6]. In veterinary medicine, cyclosporine has been widely used for dermatologic diseases and other systemic immune-mediated diseases [1,2,13,16]. Recent reviews and a meta-analysis of prospective clinical trials concluded that cyclosporine was highly effective compared with placebo and was as effective as prednisolone for treatment of atopic dermatitis in the dog [13,16].…”
mentioning
confidence: 99%
“…In veterinary medicine, cyclosporine has been widely used for dermatologic diseases and other systemic immune-mediated diseases [1,2,13,16]. Recent reviews and a meta-analysis of prospective clinical trials concluded that cyclosporine was highly effective compared with placebo and was as effective as prednisolone for treatment of atopic dermatitis in the dog [13,16]. Some reports have suggested that cyclosporine is an effective therapeutic option for CNS inflammation in dogs [1,2].…”
mentioning
confidence: 99%
“…4 Yet, a more recent study 25 using this medication at higher doses (20 mg/kg three times daily versus 10 mg/kg twice daily of the original studies 26 ) and in combination with essential fatty acids showed a marked beneficial effect. In this study, dogs receiving the combination of pentoxifylline and essential fatty acids revealed 56.75% and 47.76% reduction in clinical scores and pruritus scores on day 30, while the corresponding reduction on day 60 was 90.92% and 92.59%, respectively.…”
Section: Long-term Approach To Chronic Casesmentioning
confidence: 96%
“…4 Of these options, some are used for the management of the acute flare-up and others are best suited for the long-term approach.…”
Section: Treatment Options and Evidence Of Efficacymentioning
confidence: 99%
See 1 more Smart Citation